Instructional level moderation at improving numerical literacy skills through creative problem-solving learning models - Apriatni, Sri; Nindiasari, Hepsi; Sukirwan, Sukirwan; Khaeroni, Khaeroni (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Background: In today's ever-changing landscape, students need strong numerical literacy skills to navigate life's complexities. Recognizing that students come with various learning capabilities, often referred to as "instructional levels," educators must think outside the box when it comes to teaching methods.Aim: This study aims to 1) gauge whether creative problem solving (CPS) or scientific learning is more effective in enhancing the numerical literacy skills of MA students; 2) assess the difference in the numerical literacy progress among MA students categorized at independent, instructional, and frustration levels; and 3) explore the interplay between teaching methods and instructional levels on students’ numerical literacy development.Method: Conducted as an experimental study, this research employs a 3x2 factorial design. Participants include students from Class X IPA at MAN 2 Serang. To collect data, we used tests focused on numerical literacy as well as assessments to categorize instructional levels. A two-way ANOVA serves as the statistical approach to test our hypotheses.Result: 1) MA students exposed to the CPS method showed greater improvements in their numerical literacy skills than those who engaged in scientific learning; 2) A noticeable variance exists in the growth of numerical literacy skills among MA students at independent, instructional, and frustration levels; 3) An interaction effect was identified between the chosen teaching method and the instructional level in shaping the numerical literacy skills of MA students.Conclusion: The study concludes that creative problem-solving is more potent than scientific learning in elevating the numerical literacy of MA students. Furthermore, instructional levels play a crucial role in this improvement. A synergistic effect between the teaching approach and instructional level was also found to influence the numerical literacy outcomes.